Victims’ specific expectations arising from experiences of workplace mobbing - Mykolas DEIKUS; Jolita VVEINHARDT (Communications of International Proceedings, 2023)
The purpose of the research presented in the paper is to define key expectations of victims, arising from specific experiences of workplace mobbing. The research seeks to answer the following problem questions: What sufferings can verbal and non-verbal hostile behaviour acts cause for the victim of workplace mobbing? What personal characteristics of the individual can increase the risk of becoming the victim of workplace mobbing? What are the expectations of help for victims of workplace mobbing? The research was conducted using the semi-systematic literature review method. The research results show that the researchers focus on the experiences caused by mobbing, such as irritation, anxiety and fear, helplessness, pain, loneliness and shame. Four groups of qualities of victims of mobbing (psychological characteristics, social competency, social attitudes and distinctiveness) examined in the scientific literature have been identified. Finally, three groups of expectations among victims of mobbing (internal, interactional and external) have been distinguished. It is concluded that orientation to expectations and their better understanding helps to look at the mobbing situation, first of all, from the victim’s perspective.
Keywords: workplace mobbing; victim; support; expectations